Comparison of the quality of life of children with congenital megacolon (Hirschsprung’s disease) post transanal endorectal pull-through with other children’s surgical cases in the 5-7-years age group at Moewardi Hospital Surakarta - Agrensa, Riza S.; Suwardi; Nugroho, Hari W.; A., Ida B. Budhi S. (International Surgery Journal, 2023)
Background: Congenital megacolon (Hirschsprung’s disease) is caused by intestinal innervation abnormalities, due to failure of neuroblast migration from the proximal to the distal intestine so there is no nerve innervation in the distal intestine and causes functional ileus and hypertrophy and excessive intestinal distension. The classic triad of clinical features in neonates is late meconium expulsion, namely more than the first 24 hours, green vomiting, and an enlarged stomach. Management of congenital megacolon is divided into two, namely non-surgical treatment to overcome complications that may occur and to improve the general condition until definitive surgery and surgical treatment namely transabdominal approach (TAB), consisting of Swenson, Duhamel, Rehbein, and Soave, and transanal endorectal pull-through (TEPT). The advantages of TEPT include better cosmetic effects and shorter hospital stays. Quality of life (QoL) is a subjective perception of a person’s well-being regarding levels in his life, which includes physical, social, and psychological conditions. Methods: This research is observational analytical research with a cross-sectional approach conducted at RSUD Dr. Moewardi Surakarta during August - September 2022. Results: Patients with congenital megacolon (Hirschsprung disease) after TEPT have a worse QoL than patients without congenital megacolon (p value <0.05). All components of the pediatrics quality of life questionnaire (PedsQLTM) are influenced by the patient’s condition (p value <0.05). Conclusions: The poor quality of life should increase awareness of the importance of immediate treatment. Difficulty defecating, diarrhea, and abdominal pain can reduce the patient’s QoL after TEPT. Family dynamics and support must be prioritized to improve the QoL.